2000
DOI: 10.1038/modpathol.3880086
|View full text |Cite
|
Sign up to set email alerts
|

The Coexistence of Low-Grade Mucinous Neoplasms of the Appendix and Appendiceal Diverticula: A Possible Role in the Pathogenesis of Pseudomyxoma Peritonei

Abstract: We examined 38 appendectomies with diagnoses of mucocele, diverticulum, or adenoma to study the coincidence of appendiceal diverticula and appendiceal low-grade mucinous neoplasms and to examine the possible role of diverticula in the pathogenesis of pseudomyxoma peritonei. Invasive adenocarcinomas and retention cysts were excluded (six cases). Cases were classified as adenomas or mucinous tumors of unknown malignant potential, with or without diverticula. Medical records were reviewed for multiple parameters,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
81
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 14 publications
2
81
0
4
Order By: Relevance
“…However, the number of cases that were followed-up are few and the follow-up periods are short. In the study by Lamps et al, rupture of the diverticulum was correlated with pseudomyxoma peritonei in only one case [20]. No comment was made about the relationship between rupture of the diverticulum and periappendicular mucin without epithelium in other studies.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…However, the number of cases that were followed-up are few and the follow-up periods are short. In the study by Lamps et al, rupture of the diverticulum was correlated with pseudomyxoma peritonei in only one case [20]. No comment was made about the relationship between rupture of the diverticulum and periappendicular mucin without epithelium in other studies.…”
Section: Discussionmentioning
confidence: 88%
“…They suggested that diverticula may give a clue about underlying neoplasms [16]. In the study by Lamps et al diverticula were determined in 8 of 19 LGMNs (42%) [20]. We detected accompanying diverticula in 23 of 38 LGMN cases (60.5%).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations